Токийская невеста: роман / Амели Нотомб ; пер.с фр. Надежды Кузнецовой - Нотомб А. (Иностранка, 2011)
Экземпляры: ф.4,8 (20120402) / Инвентарный номер: 46706 / Цена: 183-38 / Авт.знак: Н 85 / ББК: И(4Фра)